Renal cancer survival in clear cell renal cancer compared to other types of tumor histology: A population-based cohort study - Teesi Sepp; Antti Poyhonen; Anneli Uusküla; Andres Kotsar; Thea Veitonmäki; Teuvo L. J. Tammela; Aleksei Baburin; Teemu J. Murtola (PLoS ONE, 2025)
Introduction Renal cancer (RC) presents a challenge with increasing incidence and mortality. This study compares RC cancer-specific survival (CSS) and overall survival (OS) based on histological type. Study design This population-based retrospective cohort study covers 1995–2017, utilizing cases from the Finnish Cancer Registry. Comorbidity, procedure and treatment information from 1995–2018 were obtained from the national health care registry, while death data originated from the national death certificate registry. RC cases were categorized by histology to analyze CSS and OS via Fine and Gray’s proportional sub-hazards model and Cox regression (adjusting for age, tumor extent, Charlson comorbidity index and treatment). Results The final cohort included 14,413 patients, predominantly ccRCC (75.5%), followed by papillary RCC (pRCC),5.8% and chromophobe RCC (chRCC) 2.1%. Univariate analysis showed better OS for non-ccRCC patients, with 5-year survival (5ySR) of 72.6% (95% CI 70.3–74.7%), compared to ccRCC (62.7%, 95%CI 61.8–63.5). Among non-ccRCC, the 5ySRs were as follows: pRCC 74.3% (95%CI 71.2–77.2), chRCC 82.2% (95% CI 77.2–86.1), sarcomatoid variants (sarcRC) 29.2% (95% CI 20.6–38.3), and collecting duct carcinoma (CDC) 23.5% (95%CI 7.3–44.9). Non-ccRCC showed improved CSS compared to ccRCC (sHR 0.69, 95% CI 0.60–0.78). Favorable CSS for chRCC (sHR 0.28, 95% CI 0.18–0.43) and pRCC (sHR 0.66, 95% CI 0.56–0.78), while sarcRC (sHR 1.83, 95% CI 1.36–2.46) and CDC (sHR 3.19, 95% CI 2.01–5.08) showed poorer CSS. Overall, non-ccRCC had a better prognosis, driven by pRCC and chRCC, whereas sarcRC and CDC had poor prognoses. CSS has improved over time, with a 62% reduction in death risk since 1995. Conclusion Our results demonstrate that the histological subtype is a powerful predictor of survival. Histology should be used more in clinical decision-making. Having a histological confirmation would tailor the selection of treatment: surgical management for aggressive and ccRCC and conservative management for less aggressive histological types.